2014
DOI: 10.1128/jb.00892-13
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive Photic Responses and Intact Genome-Wide Transcriptional Control without the KaiC Phosphorylation Cycle in the Synechococcus Circadian System

Abstract: bCyanobacteria are unique organisms with remarkably stable circadian oscillations. These are controlled by a network architecture that comprises two regulatory factors: posttranslational oscillation (PTO) and a transcription/translation feedback loop (TTFL). The clock proteins KaiA, KaiB, and KaiC are essential for the circadian rhythm of the unicellular species Synechococcus elongatus PCC 7942. Temperature-compensated autonomous cycling of KaiC phosphorylation has been proposed as the primary oscillator mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Under our experimental conditions, dark pulses of 2 or 4 h gave rise to slight phase shifts in the WT strain, whereas dark pulses of 6 h advanced the phase during the subjective day (hour 8 in LL, Fig. 2a), as reported previously 26 . Conversely, the phases of bioluminescence rhythms in kaiA − strains were much more dramatically shifted against dark pulses, especially those of 4 or 6 h (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Under our experimental conditions, dark pulses of 2 or 4 h gave rise to slight phase shifts in the WT strain, whereas dark pulses of 6 h advanced the phase during the subjective day (hour 8 in LL, Fig. 2a), as reported previously 26 . Conversely, the phases of bioluminescence rhythms in kaiA − strains were much more dramatically shifted against dark pulses, especially those of 4 or 6 h (Fig.…”
Section: Resultssupporting
confidence: 88%
“…In this study, to verify whether any specific phosphorylation state of KaiC is required for the damped oscillation, we introduced mutations into kaiC to constitutively mimic either the hypophosphorylated or hyperphosphorylated form of KaiC in kaiA − strains. When kaiA is intact, substitution of KaiC phosphorylation sites (S431 and T432) with phosphomimic glutamate residues (kaiC EE ) does not abolish transcriptional rhythms, but it sustains rhythms with a lengthened period of 48 h 26,31 .…”
Section: Resonance Of Damped Oscillation In Response To External Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies agree that the PTO (now reconstituted in another cell type [88]) is the necessary-and-sufficient core oscillator. However, even absent the KaiABC-based PTO, the TTFL is capable of driving temperature-compensated rhythmic gene expression (albeit with a long 48 hr period length) of a substantial portion of the genome [89], suggesting that while the PTO is required for robustness and proper periodicity it may cooperate with the TTFL for output. Two recent analyses have tied the slow rate of ATP hydrolysis in the PTO to rates of structural changes in the Kai proteins, via a slow peptide isomerization in KaiC [90] and a slow and rare shift between folded states of KaiB that affects its ability both to capture KaiA (and thereby promote KaiC dephosphorylation) and to bind to and activate CikA, thereby influencing output [32].…”
Section: Figurementioning
confidence: 99%
“…This view is in contrast to the dominant output model that the oscillator induces transcriptional activation rather than repression. Intriguingly, cells that express a KaiC variant unable to undergo phosphorylation cycling, poised at the stage where we now realize KaiB and SasA compete for KaiC binding, still exhibited transcriptional rhythms of gene expression, albeit with a 48-h rather than 24-h period (87). Nakahira et al showed that there is a global down-regulation of gene expression when kaiC is over-expressed (58), supporting this paradigm shift.…”
Section: A Network-centric View Of the Clockmentioning
confidence: 99%